2022
DOI: 10.3390/jcm11144022
|View full text |Cite
|
Sign up to set email alerts
|

Employing the Multivariate Edmonton Scale in the Assessment of Frailty Syndrome in Heart Failure

Abstract: Background: Frailty syndrome (FS) is a syndrome characterized by a reduction in the body’s physiological reserves as a result of the accumulation of reduced efficiency of many organs and systems. Experts of the Heart Failure Association of the European Society of Cardiology (ECS) emphasize the need to assess frailty in all patients with heart failure (HF). There is no specific scale dedicated to this group of patients. The aim of the study was to assess the occurrence of the frailty syndrome in heart failure u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The second one rates frailty by the number of functional, sensory and clinical deficits based on the Canadian Study of Health and Aging Frailty (overall 70 items) [ 12 ], which contains the 11 variables used to calculate the mFI [ 11 ]. Following these two models, other scale were developed, like the Edmonton Frailty Scale, which have been assessed also in HF and heart transplantation [ 32 ]. We must acknowledge that the mFI adopted in our study does not measure several factors, such as laboratory or motor parameters, which may have been linked to frailty and could have helped achieve a better patient description.…”
Section: Discussionmentioning
confidence: 99%
“…The second one rates frailty by the number of functional, sensory and clinical deficits based on the Canadian Study of Health and Aging Frailty (overall 70 items) [ 12 ], which contains the 11 variables used to calculate the mFI [ 11 ]. Following these two models, other scale were developed, like the Edmonton Frailty Scale, which have been assessed also in HF and heart transplantation [ 32 ]. We must acknowledge that the mFI adopted in our study does not measure several factors, such as laboratory or motor parameters, which may have been linked to frailty and could have helped achieve a better patient description.…”
Section: Discussionmentioning
confidence: 99%
“…In the other Polish studies on hospital inpatients, the incidence of frailty syndrome assessed using the Fried criteria was 54.2% [ 25 ], using the Edmonton scale—12.3% (mean age 62.6+/−9.7y) [ 36 ], and SHARE-FI (mean age 73 (68–81)y) − 39% [ 37 ]. In another Polish study, in patients hospitalized due to heart failure (mean age 71.6 ± 10.9 years), frailty frequency using the Tilburg Frailty Indicator scale was 71.62% [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we used the Edmonton Frail Scale (EFS) as a second and multi-domain instrument to assess frailty ( Supplementary Table S4 ) [31] . Rolfson et al demonstrated that the EFS is a valid tool for determining frailty when compared to the CGA and the EFS is used in several cardiac populations, including heart failure patients, in literature [32] , [33] , [34] , [35] .…”
Section: Methodsmentioning
confidence: 99%